Moisture sorption isotherm of C. nutans herbal leaves - Abdullah, Sriyana; Yusof, Yus Aniza; Abdul Karim Shah, Nor Nadiah; Mohd Salleh, Faiqa Shazeaa; Ali, Muhammad Azhar; Abdul Razak, Norawanis (EJournal Publishing, 2023)
The moisture sorption isotherms of Clinacanthus nutans (C. nutans) herbal leaves were established at three different temperatures of 30°C, 40°C, and 50°C, and water activity between 0.3–0.9 using a static gravimetric method. The results showed that equilibrium moisture content of C. nutans increased with increasing water activity at a constant temperature for both desorption and adsorption isotherms. In contrast, the equilibrium moisture content decreased when the temperature increased at a constant water activity for all isotherms. The sorption isotherms exhibited Type III behaviour or J-shaped curve according to Brunauer-Emmett-Teller (BET) classification. It was found that Guggenheim-Anderson-de Boer (GAB) and Peleg models were the best-fit to the experimental moisture isotherms. The maximum net isosteric heat of sorption values were found to be 70 kJ/mol and 13 kJ/mol for desorption and adsorption respectively. The moisture sorption isotherms established are essential for optimum design of C. nutans dryer and storage conditions.